Avaliação da resposta pulpar inicial após o uso de MTA e sulfato férrico em pulpotomias de molares de ratos - Lopes, Camila Soares (2018)
Pulpotomies with capping materials that enhance the recovery of radicular pulp health may be performed in cases of dental caries or trauma of primary teeth. However, none of the available materials present all the requirements of an ideal material. The purpose of this study was to evaluate the initial pulp response of rat molars after pulpotomy with white mineral trioxide aggregate (MTA) or 15.5% ferric sulfate (FS). Twenty-four Wistar rats, randomly distributed into 2 groups (MTA and FS) and divided according to the period of evaluation (24, 48 and 72 hours), were used. After animal euthanasia, teeth were removed in block and prepared for histological analysis. Some serial sections underwent hematoxylin and eosin (HE) staining and were assessed morphometrically regarding the inflammatory response and vascular density; other sections were subjected to immunohistochemistry for the detection of interleukin 6 (IL-6). Data were analyzed statistically (p<0.05). There was no difference in the number of inflammatory cells between MTA and FS groups, being predominantly localized at the cervical radicular third. However, differences between the periods of evaluation were detected only in MTA group, with increased inflammation at 48 hours. Vascular density was similar in both groups and over the time, with greater vascularization being observed at the medium radicular third in both groups. There was no correlation between the inflammatory status and the vascular density. Pulp connective tissue in MTA group was more organized in comparison with FS group. In both groups, there was expression of IL-6 from week to moderate in odontoblasts and inflammatory cells. Considering each group separately, there was greater IL-6 expression in the cervical radicular third of teeth treated with MTA at 24 hours and of those treated with FS at 48 and 72 hours. Comparing the groups, there was significantly greater expression for MTA group at 24 hours in the cervical third and at 72 hours in the medium and apical thirds, while the greater expression occurred in the FS group only at 24 hours in the apical third. In conclusion, there was no difference between the groups regarding the inflammatory status and vascularization, with increased inflammation in the medium radicular third at 48 hours. However, the radicular pulp of teeth treated with MTA often presented superior histological features and greater IL-6 expression.